Application of a model updating technique for health condition monitoring and damage detection of flexible structures - Pereira, Joao A. [UNESP]; Heylen, Ward; Lammers, Stefan; Sas, Paul (ASME International, 1995)
This paper discusses the application of a damage detection methodology to monitor the location and extent of partial structural damage. The methodology combines, in an iterative way, the model updating technique based on frequency response functions (FRF) with monitoring data aiming at identifying the damage area of the structure. After the updating procedure reaches a good correlation between the models, it compares the parameters of the damage structure with those of the undamaged one to find the deteriorated area. The influence of the FEM mesh size on the evaluation of the extent of the damage has also been discussed. The methodology is applied using real experimental data from a spatial frame structure.